Effectiveness of the Implementation of the Free Plowing Service Program in Tanah Datar District (Case Study of Sungai Tarab District) - Muhammad Raihan Alhazra; Sujianto Sujianto (Journal of Education Technology Information Social Sciences and Health, 2024)
The Free Plow Program, launched by the Tanah Datar District Government, aimed to provide economic assistance to farmers. However, the program faced challenges in Sungai Tarab sub-district due to issues with the associated regulations. This study conducted research to assess the effectiveness of the program and analyze the potential impact if free plow assistance was not provided to sharecroppers in Sungai Tarab. Budiani's theories of program effectiveness, including program targeting accuracy, program socialization, program objectives, and monitoring, were used as the framework for the research. A qualitative methodology, specifically a case study, was employed, with interviews, observations, and document searches. The research revealed several obstacles that impeded the implementation of the free plow program in Sungai Tarab sub-district. Among these are DTKS's outdated data on tenant farmers who are economically disadvantaged; the closure of the distribution of fuel assistance due to the prohibition of picking up petroleum with jerry cans; and no clear regulations on how assistance should be given fairly to tenant farmers who lack water. The Tanah Datar District Government is advised to optimize the distribution of farmer assistance (petroleum); supporting facilities, such as irrigation improvements and the procurement of pompanization systems around rain-fed rice fields in Sungai Tarab District